Adolescent Girls Attitudes Toward My Plate as a Strategy to Prevent Stunting - Heni Heryani; Lusi Lestari (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2025)
Introduction: Stunting is a chronic nutritional problem caused by prolonged inadequate nutrient intake and recurrent infections, leading to impaired growth and development in children. Globally, stunting remains a major public health challenge, particularly in developing countries, including Indonesia. Stunting does not only affect physical growth but also impacts cognitive development, productivity, and future health risks. Adolescents, especially girls, are an important target group in stunting prevention because they are future mothers who will determine the nutritional status of the next generation. Adopting positive attitudes and behaviors regarding nutrition during adolescence is crucial to break the intergenerational cycle of stunting. The Indonesian Ministry of Health has introduced the My Plate guidelines as a practical approach to promote balanced nutrition, emphasizing the importance of appropriate food portions that consist of vegetables, fruits, protein, and carbohydrates. Objective: This study aimed to determine adolescent girls’ attitudes toward the My Plate program as one of the strategies to prevent stunting. Method: This descriptive study involved 214 adolescent girls at SMPN 1 Ciamis, selected using accidental sampling. Data were collected using a structured questionnaire on attitudes toward My Plate. The data were analyzed using univariate methods to obtain frequency distributions. Results:  The findings showed that 112 respondents (52.3%) had negative attitudes, while 102 respondents (47.7%) demonstrated positive attitudes. Although the difference was slight, the results indicate that most adolescent girls still have a less supportive attitude toward the implementation of My Plate in daily life. Conclusion: Adolescent girls’ attitudes toward My Plate remain predominantly negative, highlighting the need for strengthened nutrition education. Schools and health services are encouraged to collaborate in conducting routine counseling on balanced nutrition and the importance of My Plate to foster more positive attitudes and support stunting prevention efforts.